Dynamic analysis of reinforced concrete plate resting on elastic foundation using state space method and refined plate theory - Trong Hiep, Nguyen (Civil and Environmental Science Journal (CIVENSE), 2023)
This paper studies the dynamic response of rectangular reinforced concrete plates on an elastic foundation by state space method. The system of differential equations of vibration of the plate is developed by using Hamilton's principle. With a single-link rectangular plate, the displacements are represented through a double trigonometric series. Use the state space method to find the plate vibrational responses. The calculation examples are performed to calculate the displacement and stress of the plate with different structural parameters, thereby evaluating the influence of these parameters.